Techno-economic Evaluation of Deploying CCS in SMR Based Merchant H2 Production with NG as Feedstock and Fuel. (July 2017) - Collodi, Guido; Azzaro, Giuliana; Ferrari, Noemi; Santos, Stanley
Abstract: Hydrogen is a crucial raw materials to other industries. Globally, nearly 90% of the hydrogen or HyCO gas produced is consumed by the ammonia, methanol and oil refining industries. In the future, hydrogen could play an important role in the decarbonisation of transport fuel (i.e. use of fuel cell vehicles) and space heating (i.e. industrial, commercial, building and residential heating). This paper summarizes the results of the feasibility study carried out by Amec Foster Wheeler for the IEA Greenhouse Gas R&D Programme (IEA GHG) with the purpose of evaluating the performance and costs of a modern steam methane reforming without and with CCS producing 100, 000 Nm 3 /h H2 and operating as a merchant plant. This study focuses on the economic evaluation of five different alternatives to capture CO2 from SMR. This paper provides an up-to-date assessment of the performance and cost of producing hydrogen without and with CCS based on technologies that could be erected today. This study demonstrates that CO2 could be captured from an SMR plant with an overall capture rate ranging between 53 to 90%. The integration of CO2 capture plant could increase the NG consumption by -0.03 to 1.41 GJ per Nm 3 /h of H2 . The amount of electricity exported to the grid by the SMR plant is reduced. The levelised cost of H2 production could increase by 2.1 to 5.1 € cent per Nm 3 H2 (depending on capture rate and technology selected). This translates to a CO2 avoidance cost of 47 to 70 €/t.